THE DEVELOPMENT OF STUDENTS’ COMPETENCES THROUGH LIBRARY AND INTERNET RESEARCH SKILLS - Abdullaeva, Lola Tokhirovna (Universitas Muhammadiyah Makassar, 2024)
According to a presidential decree dated 20 June 2006 “On the organization of Information and library services for the population of Uzbekistan”, the libraries of higher education institutions began to function as Information Resource Centers (IRCs).Developing students’ library skills is most important in high educational establishments, teachers both librarians should be aware of how to prepare students for doing independent research out of classrooms and campus so that students can attain and develop skills at the best and most relevant times.It has become obvious that developing students’ library research skills is vital in Universities, institutes as these skills when used in integrity with Information skills based on Communication technologies may lead to better academic achievements, goals, high productivity and makes students be more autonomous in gaining knowledge, developing their competencies and should be included into Curricula as a part of study program from undergraduate levels and above.